Cutting back, Dividing up and Segmenting: Colonial Knowledge and its Post-colonial Extension in Mozambique - Pereira, Rui M. (Revista de Antropología Social, 2016)
Anthropology was politically manipulated in Mozambique, more than anywhere else in the Portuguese colonies, to step in, to rank and organize all dimensions and fields of the African society in the colonial standard of domination. Successive attempts to codify and accommodate “indigenous practices and customs” in Mozambique during the second half of the 19th century were aligned with the needs of the Portuguese colonial policy of integrating and resolving a set of contradictions and challenges that emerged from the management and domination of the colonised population. In the last decade of the 19th century, military campaigns for pacification changed the supposed established period of adjustment, emphasizing the need of ethnographic studies for emphasizing the stale differences in civilization development as a means of domination. Consecutive law orders, (“indigenous statutes”), consecrated the subalternity and the supposed inferiority of the African populations in Mozambique. Therefore, the ethnographic knowledge of the Mozambique population was consolidated in the prevalent existence of an irreducible distinction “of civilization”.The coloniality of anthropological knowledge left a long lasting framework of segmentation, classification and hierarchical organisation of African societies —which is still present nowadays—. This was dramatically expressed during the Mozambican civil war that followed independence (1977-1992), and continues to be alive in part of the discourse that pervades the political tension in Mozambique over the past few years.
Keywords: Portuguese Colonialism; Mozambique; Colonial Anthropology; customary law; ethnicity and nationalism.